Staphylococcal scalded skin syndrome caused by methicillin-resistant Staphylococcus aureus with superadded fungal infection in a neonate - Gogoi, Mayuri; Borah, Nilakshi; Sharma, Ajanta (International Journal of Research in Medical Sciences, 2017)
Staphylococcal scalded skin syndrome (SSSS) or acute staphylococcal epidermolysis is an exfoliative skin disease and a toxin mediated staphylococcal infection affecting mostly neonates and adolescents. We describe here a case of 10-day old full term, vaginally delivered baby weighing 1530gms presenting with erythematous lesions first developing on the face and later spreading to the entire body for the last 6 days. The mucosal areas were spared. Blood culture of the patient revealed growth of Methicllin Resistant Staphylococcus aureus (MRSA). Culture from the skin lesions also revealed growth of MRSA with similar antibiotic sensitivity pattern. Fungal culture from the skin lesions revealed growth of Candida tropicalis. The diagnosis of SSSS was based on clinical criteria and microbiological findings.